Analisis Pengaruh Desentralisasi Fiskal dan Retribusi Daerah terhadap Inflasi di Pulau Jawa - Yustirania Septiani; Azril Arrasyd; Muhammad Fakhriy Wafiy; Naufal Hana Alfian (Universitas Diponegoro, 2024)
The aim of this research is to determine the extent to which fiscal decentralization and regional retribution affect the inflation rate in the provinces of Banten, West Java, Central Java, DI Yogyakarta, and East Java. The research can serve as a reference for the government in managing fiscal decentralization funds (DBH, DAU, and DAK) as well as regional retribution. The researchers used a quantitative approach and the method employed in this study is multiple linear regression using the Fixed Effect Model (FEM). The results show that the ratio of DBH to inflation has a negative effect on inflation in the provinces of Banten, West Java, Central Java, DI Yogyakarta, and East Java. The ratio of DAU to inflation also has a negative effect, the ratio of DBH to inflation has a negative effect, and regional retribution has a positive but insignificant effect on inflation. The study examines the extent of the effect of fiscal decentralization funds (DBH, DAU, and DAK) and regional retribution on inflation in the provinces of Java Island, namely Banten, West Java, Central Java, DI Yogyakarta, and East Java, excluding DKI Jakarta. This is because the fiscal gap in general allocation funds in DKI Jakarta is covered by regional income, so there is no transfer of central income to DKI Jakarta in the form of general allocation funds.